Localization of ventricular activation origin using patient-specific geometry: Preliminary results - Zhou, Shijie; Sapp, John L; AbdelWahab, Amir; Šťovíček, Petr; Horáček, B Milan (Journal of cardiovascular electrophysiology, 2018)
BACKGROUND AND OBJECTIVES: Catheter ablation of ventricular tachycardia (VT) may include induction of VT and localization of VT-exit site. Our aim was to assess localization performance of a novel statistical pace-mapping method and compare it with performance of an electrocardiographic inverse solution. METHODS: Seven patients undergoing ablation of VT (4 with epicardial, 3 with endocardial exit) aided by electroanatomic mapping underwent intraprocedural 120-lead body-surface potential mapping (BSPM). Two approaches to localization of activation origin were tested: (1) A statistical method, based on multiple linear regression (MLR), which required only the conventional 12-lead ECG for a sufficient number of pacing sites with known origin together with patient-specific geometry of the endocardial/epicardial surface obtained by electroanatomic mapping; and (2) a classical deterministic inverse solution for recovering heart-surface potentials, which required BSPM and patient-specific geometry of the heart and torso obtained via computed tomography (CT). RESULTS: For the MLR method, at least 10-15 pacing sites with known coordinates, together with their corresponding 12-lead ECGs, were required to derive reliable patient-specific regression equations, which then enabled accurate localization of ventricular activation with unknown origin. For 4 patients who underwent epicardial mapping, the median of localization error for the MLR was significantly lower than that for the inverse solution (10.6 vs. 27.3 mm, P = 0.034); a similar result held for 3 patients who underwent endocardial mapping (7.7 vs. 17.1 mm, P = 0.017). The pooled localization error for all epicardial and endocardial sites was also significantly smaller for the MLR compared with the inverse solution (P = 0.005). CONCLUSIONS: The novel pace-mapping approach to localizing the origin of ventricular activation offers an easily implementable supplement and/or alternative to the preprocedure inverse solution; its simplicity makes it suitable for real-time applications during clinical catheter-ablation procedures.
Keywords: Imaging, Three-Dimensional; mapování potenciálů tělesného povrchu; Body Surface Potential Mapping; Humans; Models, Anatomic; 12-lead ECG; modely kardiovaskulární; Models, Cardiovascular; pace-mapping; lidé; katetrizační ablace; catheter ablation; ventricular tachycardia; body surface potential mapping; zobrazování trojrozměrné; komorová tachykardie; Catheter Ablation; anatomické modely; Tachycardia, Ventricular